Tingkat Pengetahuan Remaja Putri Tentang Dampak Pernikahan Dini Pada Kesehatan Reproduksi di SMAN 1 Katingan Kuala: The Level of Knowledge of Young Women About the Impact of Early Marriage on Reproductive Health at SMAN 1 Katingan Kuala - Sri Wahyuni, Lulu Handayani; Nita Theresia; Baharuddin Yusuf (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2025)
Adolescence is a period of rapid growth and development both physically, psychologically and intellectually so that adolescents face many decision-making processes, one of which is about reproductive health and marriage. Central Kalimantan Province occupies one of the highest in Indonesia in marriage perpetrators aged 15 to 19 years with 52.1 percent cases. The purpose of study to find out the level of knowledge of young girls about the impact of early marriage on reproductive health at SMAN 1 Katingan Kuala. Research uses a quantitative descriptive research method with startified random sampling of 61 respondents. The results the highest level of knowledge in the good categories 54 respondents (88.5%), and the knowledge based on the most information sources the internet with good categories with 25 respondents (83.3%). The knowledge of teenagers at SMAN 1 Katingan Kuala is included in the good category, the thing that affects is the ease of the internet so that it facilitates obtaining educational information about reproductive health for teenage girls.